The effective use of Geographic Information System (GIS) in the planning departments, Kuala Lumpur City Hall (KLCH) - Mohd. Hussain, Mohd. Ramzi; Johar, Foziah (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
The paper presents the important factors associated with the effective use of GIS at the Department of Urban Planning (DUP) and the Master Plan Department (MPD) of the Kuala Lumpur City Hall (KLCH) Malaysia. The development of GIS has progressed dramatically in recent years and its use has proliferated in government planning departments in Malaysia. The majority of the information utilised for planning activities such as development control has a geographical component. The aim of the paper is therefore to identifY and investigate the level of GIS usage at local planning departments in Malaysia and how it could be used effectively for planning activities. This paper employed a combination of a case study, a semistructured interview, and a survey questionnaire and observations of the activities of the department. The findings demonstrate that the skill, knowledge and training influence the planning staff to use GIS effectively. At the same time, GIS has various impacts, such as benefits and problems, on the planning departments and the staff involved. It is proved that the manner in which these factors interact with the GIS determines the processes which affect the effective utilisation process of automated systems.